2011
DOI: 10.1002/uog.8878
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal management of congenital infantile fibrosarcoma: unexpected outcome

Abstract: We report the case of a large leg tumor in a fetus at 36 weeks of gestation. The tumor 's location, ultrasound CASE REPORTA 31-year-old woman, gravida 2 para 0, was referred to our hospital after a third ultrasound examination at 36 weeks of gestation revealed a large tumor on the right leg of the fetus (Figure 1a). The patient had conceived spontaneously and had no family history of any malformation. This anomaly was not present on previous ultrasound examinations. The tumor measured 90 × 80 mm and was poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 10 publications
(6 reference statements)
0
18
0
Order By: Relevance
“…Dumont et al [12] reported a case of a fibrosarcoma found in a 36 week gestational age fetus. Ulceration in utero may cause various complications including polyhydramnios, torsion, anemia, hemorrhagic shock, hemolysis, as well as compression of adjacent organs and cardiac insufficiency; any of which could threaten intrauterine life.…”
Section: Discussionmentioning
confidence: 99%
“…Dumont et al [12] reported a case of a fibrosarcoma found in a 36 week gestational age fetus. Ulceration in utero may cause various complications including polyhydramnios, torsion, anemia, hemorrhagic shock, hemolysis, as well as compression of adjacent organs and cardiac insufficiency; any of which could threaten intrauterine life.…”
Section: Discussionmentioning
confidence: 99%
“…It is locally aggressive with an increased rate of local recurrence, but systemic metastasis is very rare. Most infantile fibrosarcomas are diagnosed postnatally, but there are increasing reports of antenatally diagnosed cases [11,12]. There appear to be no advantage to preterm delivery of these patients except if there is associated hydrops and delivery by cesarean section is indicated only in those with large tumors that are likely to obstruct delivery.…”
Section: Discussionmentioning
confidence: 94%
“…With the widespread use of routine antenatal ultrasonography, reported cases with fibrosarcoma detected prenatally have increased (Table 1) [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Unlike postnatally diagnosed cases, prenatal CIFs are located in various sites, and only 3 of 14 cases occurred in limbs.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, CIF should be considered in the differential diagnosis of any soft tissue mass found during fetal sonography. Recently, the combination of ultrasound and magnetic resonance imaging has allowed for the prenatal diagnosis of CIF [5]. Congenital infantile fibrosarcoma is usually successfully treated with surgery.…”
Section: Discussionmentioning
confidence: 99%